Ovulation: the female reproductive tract, the ovary, and the ovulatory follicle - Duffy, Diane M. (Henry Stewart Talks, 2021)
Female reproductive tract and the ovary, Structural transformations of the ovulatory follicle, Mitosis and meiosis, The oocyte and cumulus